Causal Effects of Parent Number Talk on Preschoolers' Number Knowledge. Issue 6 (9th August 2020) - Gibson, Dominic J.; Gunderson, Elizabeth A.; Levine, Susan C.
Abstract : Individual differences in children's number knowledge arise early and are associated with variation in parents' number talk. However, there exists little experimental evidence of a causal link between parent number talk and children's number knowledge. Parent number talk was manipulated by creating picture books which parents were asked to read with their children every day for 4 weeks. N = 100 two‐ to four‐year olds and their parents were randomly assigned to read either Small Number (1– 3), Large Number (4– 6), or Control (non‐numerical) books. Small Number books were particularly effective in promoting number knowledge relative to the Control books. However, children who began the study further along in their number development also benefited from reading the Large Number Books with their parents.